Free Speech and the Case for Regulating Online Reviews of Professional Services in the United States - Richard L Pate; Claudio Schapsis (Law, Technology and Humans)
The relevance of online reviews to businesses is increasing exponentially. Firms have been forced to recognise that online reviews have become a necessary method of attracting new consumers. In contrast to traditional advertising, however, businesses do not control online reviews; instead, individual consumers control them. The involuntary relinquishment of this control is especially problematic to providers of professional services simply because the assessment of professional services is complicated. The primary issues stem from the inherent characteristics of services – intangibility, variability, perishability and inseparability – combined with the asymmetry in the review process. These factors contribute to a significant imbalance, where negative reviews disproportionately impact businesses, often with minimal accountability for the reviewer. This disparity is exacerbated by the permanence and widespread dissemination of online reviews, which can continue to affect a business long after the initial issue has been resolved. Notwithstanding their defective nature and their very significant negative impact on individuals and markets, online reviews are afforded the status of protected free speech. This article argues that the traits of reviews of professional service specifically resemble those of the non-rebuttable type of speech included in the categories of unprotected speech. As such, this article argues that online reviews of professional services should be regulated to safeguard the reputation and livelihood of professionals from unscrupulous, undiscerning reviewers.